A survey of sexual and reproductive health in men with cystic fibrosis: new challenges for adolescent and adult services. Issue 4 (24th March 2005) - Sawyer, S M; Farrant, B; Cerritelli, B; Wilson, J
Abstract : Background: Improved survival dramatically alters the consequences of adult co-morbidities in men with cystic fibrosis (CF) such as male infertility. Few studies have systematically addressed the impact of sexual and reproductive health issues in these men or considered the implications for healthcare delivery. Method: A descriptive cohort study was undertaken using a sexual and reproductive health survey of men from a large adult CF centre, including men with lung transplantation. Results: The mean (SD) age of the 94 men (response rate 75%) was 30.5 (7.6) years. 94% knew that men with CF had reduced fertility. Men first heard about infertility later than desired (p<0.001) and only 53% heard from their preferred source. Men who were told about infertility when older were more likely to be upset than those told earlier (p<0.01). 53% of men had undergone semen analysis: 68% of men who had not been tested wanted semen analysis. 73% believed semen analysis should occur before 18, but the youngest age of testing was 24 years. In adolescence, one in three men had assumed they did not need to use condoms and one in 10 had confused infertility with impotence. 66% of men wanted more information on reproductive options and 84% wanted children. Seventeen men were parents by natural conception (n = 1), micro-epididymal sperm aspiration (n = 6), donor sperm (n = 9), and through step children (n = 1). Conclusions: Men with CF desire more sexual and reproductive health information. Earlier discussion of sexual and reproductive health is indicated in paediatric settings, and semen analysis should be routinely offered. In adult services greater discussion of reproductive health options is indicated.